The role of sulfate in aerobic granular sludge process for emerging sulfate-laden wastewater treatment. (1st November 2017) - Xue, Weiqi; Hao, Tianwei; Mackey, Hamish R.; Li, Xiling; Chan, Richard C.; Chen, Guanghao
Abstract: Sulfate-rich wastewaters pose a major threat to mainstream wastewater treatment due to the unpreventable production of sulfide and associated shift in functional bacteria. Aerobic granular sludge could mitigate these challenges in view of its high tolerance and resilience against changes in various environmental conditions. This study aims to confirm the feasibility of aerobic granular sludge in the treatment of sulfate containing wastewater, investigate the impact of sulfate on nutrient removal and granulation, and reveal metabolic relationships in the above processes. Experiments were conducted using five sequencing batch reactors with different sulfate concentrations operated under alternating anoxic/aerobic condition. Results showed that effect of sulfate on chemical oxygen demand (COD) removal is negligible, while phosphate removal was enhanced from 12% to 87% with an increase in sulfate from 0 to 200 mg/L. However, a long acclimatization of the biomass (more than 70 days) is needed at a sulfate concentration of 500 mg/L and a total deterioration of phosphate removal at 1000 mg/L. Batch tests revealed that sulfide promoted volatile fatty acids (VFAs) uptake, producing more energy for phosphate uptake when sulfate concentrations were beneath 200 mg/L. However, sulfide detoxification became energy dominating, leaving insufficient energy for Polyhydroxyalkanoate (PHA) synthesis and phosphate uptake when sulfate content was further increased. Granulation accelerated with increasing sulfate levels by enhanced production of N -Acyl homoserine lactones (AHLs), a kind of quorum sensing (QS) auto-inducer, using S-Adenosyl Methionine (SAM) as primer. The current study demonstrates interactions among sulfate metabolism, nutrients removal and granulation, and confirms the feasibility of using the aerobic granular sludge process for sulfate-laden wastewaters treatment with low to medium sulfate content. Graphical abstract: Highlights: Various in sulfate concentrations slightly affected COD and ammonia-N removal. P removal was favored at moderate sulfate content but inhibited at high condition. Sulfate affects allocation of energy between sulfide detoxification and P removal. Sulfate stimulates synthesis of QS auto-inducers and granulation.